Modeling the reliability of a group membership protocol for dual-scheduled time division multiple access networks - Valério Rosset (2012)
We present reliability models for a group membership protocol designed for TDMA networks such as FlexRay, a protocol that is likely to become the de facto standard for next generation automotive networks. The models are based on discrete-time Markov chains and consider a comprehensive set of fault scenarios. Furthermore, they are parametric allowing for a sensitivity analysis. The results, obtained by a numeric solution of the models using the PRISM model-checker, show that they are computationally practical for realistic configurations and that the GMP can achieve reliability levels in the range required for safety critical applications.